Registos geomorfológicos e sedimentares do Plio-Plistocénico de Peniche - Atouguia da Baleia Geomorfological and sedimentary records of the Plio-Pleistocene of Peniche - Atouguia da Baleia - Cunha, Pedro (2019)
A characterization and interpretation of the Pliocene and Pleistocene geomorphological and sedimentary records of Peniche - Atouguia da Baleia littoral are here presented. The methods comprised literature review but also geomorphology, lithostratigraphy and sedimentology. Several wave-cut surfaces were characterized and mapped, respectively, at: 33-36 m, poorly preserved and considered produced by the important marine incursion dated as 3.7 Ma; 24-28 m, very large, that could correlate with the MIS9e (ca. 340-300 ka) and covered by pebbly sands with an “old” Acheulian industry; 15-19 m, that could correlate with the MIS7 (245-185 ka), covered by pebbly sands with an Acheulian industry; and 4-7 m, with a marine conglomerate, clearly related with the MIS5 (high sea-level at ca. 130-80 ka and temperate climate). The succession of aeolian fine sands intercalated with levels rich in fossils and Mousterian artefacts correlates with the interval 80-12ka (MS4, MS3 and MSI2), coeval with a low sea-level and cold climate conditions.